Design of PI and Fuzzy Logic Controllers for Distribution Static Compensator - S.R. Reddy; P.V. Prasad; G.N. Srinivas (Institute of Advanced Engineering and Science, 2018)
This paper presents study of distribution static compensator (D-STATCOM) for compensation of reactive power, harmonic distortion mitigation and load balancing in three phase three wire nonlinear load distribution system. The proposed control algorithm is developed based on synchronous reference frame theory using PI and FUZZY logic controller. The obtained reference current signal from control algorithm is compared in hysteresis band current controller for better switching of D-STATCOM. The performance of DSTATCOM with PI and fuzzy logic controller is also analysed and compared for DC voltage regulation and harmonic distortion mitigation .The proposed method is provided effective compensation for reactive power, harmonic distortion mitigation and load voltage balancing. The simulation results are obtained using MATLAB/SIMULINK soft ware.